The public-private character of United States central banking - Rowe, J. Z. (New Brunswick, N.J.: Rutgers University Press, 1966)
J. Z. Rowe has written a highly condensed descriptive account of how the public-private character of central banking evolved in the United States. About one-half of the book is devoted to tracing the origins of the present organizational arrangements and the modifications which have been made. The second half of the book describes changes in the ownership and management of foreign central banks since World War I and reviews briefly some recurring issues which still generate controversy among those wishing to change the structure of the Federal Reserve System.
Includes bibliographical references: p. [199]-206 and index.
rpm 03/05/2018
Loans
Keywords: Federal Reserve banks; Banks and banking, Central; United States